Autophagy Regulates Endoplasmic Reticulum Homeostasis and Calcium Mobilization in T Lymphocytes - Jia, Wei (2010)
Macroautophagy (hereafter referred to as autophagy) is an evolutionarily conserved intracellular bulk degradation pathway that plays critical roles in eliminating intracellular pathogens, presenting endogenous antigens, and regulating T lymphocyte survival and proliferation. In this study, we have investigated the role of autophagy in regulating the ER compartment in T lymphocytes. We found that ER content is expanded in mature Atg7-deficient T lymphocytes. Atg7-deficient T cells stimulated through the T cell receptor display impaired influx, but not efflux, of calcium, and ER calcium stores are increased in Atg7-deficient T cells. Treatment with the ER sarco/endoplasmic reticulum Ca(2+)-ATPase (SERCA) pump inhibitor thapsigargin rescues the calcium influx defect in Atg7-deficient T lymphocytes, suggesting that this impairment is caused by an intrinsic defect in ER. Furthermore, we found that the stimulation-induced redistribution of STIM-1, a critical event for the store-operated Ca(2+)-release activated Ca(2+) (CRAC) channel opening, is impaired in Atg7-deficient T cells. Together, these findings indicate that the expanded ER compartment in Atg7-deficient T cells contains increased calcium stores, and the inability of these stores to be depleted causes defective calcium influx in these cells. Our results demonstrate that autophagy plays an important role in maintaining ER and calcium homeostasis in T lymphocytes.